The effects of reward system on employee performance / Nurul Asyiqin Noorazem, Sabiroh Md Sabri and Eliy Nazira Mat Nazir - Noorazem, Nurul Asyiqin; Md Sabri, Sabiroh; Mat Nazir, Eliy Nazira (Universiti Teknologi MARA, Perlis, 2021)
Reward system which consists of financial rewards and non-financial rewards has become essential to an organization in managing employees' performance. Motivated employees can be a significant factor in organizational success. When employees are motivated to work at higher levels of productivity, the organization as a whole will run more efficiently and is more effective at reaching its goals. Literature review of the previous studies has proven that a reward system can motivate and subsequently increase employees' performance. Reward system comes in many forms, for example, intrinsic rewards and extrinsic rewards. Thus, the organization must critically understand what types of reward system can motivate the employee to perform well in their job. The purpose of this research is to investigate the effects of a reward system in an organization on employee performance. The variable tested in this study includes salary, bonuses, appreciation and medical benefits. This study adopted a quantitative approach where 132 sets of questionnaires were distributed to the participants selected using convenience sampling. Data were then analyzed using SPSS software and a few analyses were carried out such as correlations analysis and regression analysis. The results show that all variables have a significant impact on employees' performance. The results of this study can be used by the organization to improve its reward system and to ensure it could help in increasing the employees' performance.